Experimental study of mooring forces on the multi-float WEC M4 in large waves with buoy and elastic cables. (15th December 2022) - Stansby, Peter; Draycott, Sam; Li, Gangqiang; Zhao, Chenyu; Carpintero Moreno, Efrain; Pillai, Ajit; Johanning, Lars
Abstract: Experiments have been undertaken in a wave basin with the hinged attenuator-type wave energy converter M4 in a 6-float configuration with two hinges for power take off (PTO), moored to a single-point buoy. This follows previous experiments with inelastic cables giving very high snap loads. The PTO was disengaged for these tests. The aims are i) to use the elastic mooring cable to reduce the snap loads of the M4 system, with two elastic stiffnesses tested, and ii) to study the system's dynamic response with a basic mooring configuration under intermediate to large waves. Mooring loads at the fairlead and the bed, and relative pitch angle between floats were measured. Numerical simulations using two different models were carried out, and the results were compared against the experiment results. For very large waves, the floats showed occasional deck submergence (dunking) limiting relative angular motion as wave height increases, in effect providing a passive end stop. The largest peak relative angle was just less than 40°. The extreme snap loads were up to 1/6th of those with inelastic cables. Spectral analyses of relative pitch angle and mooring force were made and shown to be quite different and complex. Highlights: Elastic cables to mooring buoy for multi-float WEC in extreme waves investigated. In very large waves overtopping limited relative pitch angular response to 40° Elastic cables reduced snap force by factor up to about 6 below inelastic. Increasing cable elasticity reduced snap forces. Mooring force spectra showed peaks at pitch and peak wave frequencies.